Study Of Claims For Compensation Of Damage To Coral Reef Ecosystem Due To Vessel Grounded In The Waters Area Of Cilik Island, Karimunjawa Subdistrict, Jepara Regency, Central Java Province - Wahyudin, Yudi (Universitas Djuanda, 2020)
The purpose of this research is to conduct a claim of compensation claim for damage to the coral reef ecosystem as a vessel grounded in the waters of Cilik island, Karimunjawa Subdistrict, Jepara Regency, Central Java Province. The research method of this study conducted using survey and case of study. The analyses used by this study was economic valuation of ecosystem services loss, cost of coral reef restoration and cost of verification and dispute resolution. The result of this study showed that the total claim of compensation amounted IDR 3,067,031,155.96 (USD 227,466.52) for compensating the area of coral reef damage 111.69 square meters, i.e. IDR 635,525,318.46 for losing of coral reef ecosystem services, IDR 2,181,505,837.50 for cost of coral reef restoration, and IDR 250,000,000.00 for verification and dispute resettlement cost. This claim of compensation delivered as an effort to force the responsibility of the vessel owner and to restore the area of coral reef damage in the future.